Mulheres policiais nas unidades operacionais da PMSE : surpresas e mobilidade em meio às práticas ostensivas - Braga, Élida Damasceno (2012)
This dissertation analyzed the daily life of policewomen who work in operational service of the military police of Sergipe. Sought to understand the strategies proposed by the power relations established in the context of work, in order to list possible situations of disrespect and discrimination, considering the model of manhood still be prevalent in everyday police practices. The search took as central proposal of work performed by women police officers who are embedded in the operating units, as is the case of shock Battalion, unit observed by analyzing the dynamics that emerge from social relationships. In this sense, the problem took place around understanding how the work of women in operational units, which are places constructed microwave counter action in your templates, or is seen as male strongholds, is characterized in the context of gender and power relations that are established. In addition to the observations in the field, nine interviews were conducted with women who work or worked in operational policing. The dissertation was structured in three chapters. The first deals with the conditions for the inclusion of women in the police, the aspects involving the socialization process specific police institutions. Also presented are the pillars that upholds this order and the parameters that support the power relationships that develop. Gender issues are discussed, as well as the Justice of the quest for social recognition. The second chapter presents a general approach of studies on women in police institutions, women in the world of work, reaching typically masculine professions. It then presents the Military Police context of Sergipe, the insertion of women police officers, a brief history of shock Battalions Brazil level and Sergipe, their everyday actions to reach the theoretical approaches that address the standards and procedures necessary for the proper functioning of the operational units as well as the skills/abilities required for the performance of police work imposed to that body. In the third chapter, prioritize the gender social relations that are established under the DPO from data obtained in the research in order to understand them in accordance with the established theoretical parameters. This dissertation allows you to show that the participation of working women is wrapped by the operational PM diversity of established powers, by the non-recognition of certain actions at the expense of maintaining the current model of masculinity, but also points to new ways of doing the policing. Women unite to the model already established, extending them artfully with the female attributes such as flexibility and attention. With this increase the mobility of actions, innovating and surprising labour practices and in social interactions.